Development of social isolation and social network assessment tool for older adults: A Delphi survey - Ah-Ram Kim; Kang-Hyun Park (PLoS ONE, 2025)
Objective Social Isolation and network are crucial factors which affect the quality of life and overall health of older adults. Therefore, in the field of health promotion, there’s a growing attention to assess and evaluate the social health including social isolation and network of older adults. This study aimed to develop a Social Isolation and Social Network (SISN) evaluation tool that comprehensively measure the social isolation and network of older adults. Methods Between April and June 2024, we gathered insights from 23 experts in lifestyle and health. Based on the previous research, a two-round Delphi survey was conducted to obtain expert consensus on key assessment components. In the initial survey, we collected expert’s opinions through open and closed-ended questions about social isolation and social network evaluation items. After the first survey, we corrected several items that didn’t meet the Content Validity Ratio (CVR) standard before proceeding. We presented the first survey’s findings to an expert panel, leading to a consensus. Results The initial Delphi round produced 32 items and the second round resulted in 30 items after adjusting those with CVR scores of 0.37 or less. The final CVR was 0.87 with a convergence of 0.87, a consensus level of 0.31 and stability level of 0.12. Conclusion This study successfully developed a comprehensive social isolation and social network assessment using a modified Delphi technique. The 30 items are categorized into three sections. The SISN is able to provide a systematic approach to evaluate social isolation and social network of older adults. Future studies should be conducted to examine the reliability and validity.